Value-relevance of accounting numbers : an empirical investigation of purchased goodwill / Muhd Kamil Ibrahim ... [et al.] - Ibrahim, Muhd Kamil; Mohd Said, Marzita; Abd Latif, Radziah; Abd Shukur, Zaleha (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
We examine the value-relevance of accounting numbers in the balance sheet to investors. Specifically, we investigate the association between purchased goodwill and the value placed on the firm by the stock market. An equity valuation model based on the modified balance sheet identity is used to permit purchased goodwill, other assets and liabilities to have separate empirical coefficient values. This study finds evidence consistent with the notion that be market incorporates the information on purchased goodwill in the valuation of a firm and results also show that the market seems to perceive purchased goodwill at least with a value equal to other assets. Several empirical extensions are explored to examine whether the basic finding can be made more robust.